Measuring family functioning: validation and adaptation of the family APGAR into Indonesian - Edi Sampurno Ridwan; Raden Jaka Sarwadhamana; Winda Rofiyati (Alma Ata University Press, 2023)
Background: Family function is an important part of family caring particularly for those with aged people in the household. Understanding family functioning is imperative. A valid and reliable tool for measuring the family functioning of Indonesian family caregivers is limited. Objectives: This study aimed to examine cross-cultural adaptation, validity, and reliability of the Indonesian version of the family APGAR.    Methods: A cross-sectional design was performed as a part of a study measuring subjective family readiness for long-term care at home. A total of 125 family caregivers who were caring for older family members completed face-to-face interviews. A five-items of the family APGAR were translated, validated, and tested its reliability using standardized methods. The correlation matrix was performed to identify item correlations prior to the validation process. Hypothesis testing used a significance value of P = < 0.05 with a confidence interval (CI = 95%). The statistical test was performed using STATA14 statistical software. Results: In 125 respondents with a mean age of 52.60 years (CI = 12. 29) were interviewed. The respondents were mostly female 84 (62.20%), employed (85/68.00%). Item test correlation was ranging from 0.77 to 0.90 and the average item correlation was 0.61. Pearson coefficients were presented. The coefficient of scale reliability was Cronbach alpha 0.89. Conclusions: The Indonesian version of the family APGAR was a valid and reliable tool used for measuring family functioning among Indonesian. Further study on the use of the instrument in different settings and community characteristics was suggested using categorical level from previously measured.